Assessment of knowledge, attitude, and practice toward first aid management of choking hazards among Eastern Province Saudi adults: an observational study - Thirunavukkarasu, Ashokkumar; Alanazi, Abdulrahman Raji; Al-Rasheedi, Abdullah N.; Alruwaili, Danah Khalid; Abdel-Salam, Doaa Mazen; Alriwely, Nasser Saleh; Alruwaili, Abdulrahman Fayez J.; Alanazi, Abdulhadi Abdullah Z.; Alruwaili, Sultan Farhan O.; Alruwaili, Abdulaziz Raja R. (Frontiers in Public Health, 2024)
Background and aim Childhood choking is a global health concern that mainly affects children under the age of 5 years. The parent’s and caretaker’s responsibility is critical in the children’s lives and can potentially influence the result of at-home injuries such as choking. We aimed to assess the knowledge, attitude, practice, and associated factors of first aid management toward choking hazards among Saudi adults from the Eastern Province. Methods The present analytical study was carried out among 390 Saudi adults attending different primary health centers in the Eastern Province of Saudi Arabia. We used a standard and validated data research topic tool to assess knowledge, attitude, and practice. Spearman’s correlation was applied to determine the correlation between each section, while binomial logistic regression analysis was applied to identify the associated factors. Results We observed knowledge, attitude, and practice scores in 43.3, 38.9, and 36.4% of the participants, respectively. Furthermore, positive correlations between knowledge and attitude (rho = 0.42, p = 0.001), between knowledge and practice (rho = 0.57, p = 0.001), and between attitude and practice (rho = 0.41, p = 0.001) were revealed in our survey. The knowledge of the participants was significantly higher with the age group of 30–40 years [adjusted odds ratio (AOR) = 3.67 (1.94–4.65), p = 0.001] and participants who received training in first aid management [AOR = 1.64 (1.12–2.49), p = 0.037]. This study found that males [AOR = 0.36 (0.21–0.63), p = 0.001] and those working in the private sector [AOR = 0.61 (0.31–0.87), p = 0.018] had significantly lower attitudes. Conclusion Our results underscore the importance of continuous health education initiatives and training courses at primary health care centers regarding first aid management of choking hazards to improve awareness and practices. Furthermore, we recommend prospective multicenter studies to address region-specific knowledge gaps.